A resonance raman study of the higher-lying electronic states of styrene vapor - Ziegler, Lawrence; Varotsis, Constantinos (My University, 1986)
Resonance Raman spectra of styrene vapor excited in the S2 /S3 and S4 absorption systems are reported. The lack of double bond torsional scattering activity is taken as evidence of high barriers to rotation in all the excited states examined. Consequences for styrene photoisomerization are discussed. Excitation to S2/S3 is delocalized in nature, while S4 excitation is benzene-like. The observed scattering intensities are largely in agreement with the jet absorption analysis and the results of Franck-Condon calculations
Keywords: Photoisomerization; Raman spectroscopy; Raman effect; Chemistry; Resonance